A decision support tool for landfill methane generation - Emkes, Harriet (Cranfield University, 2013)
This paper focuses on providing a decision support tool (DST) to enhance methane generation at individual landfill sites. To date there is no decision support tool (DST) available to provide landfill decision makers with clear and simplified information for decision makers to understand what is happening within a landfill site, to assess its performance and to be aware of potential remedies to any issues. The current lack in understanding stems from the complexity of the landfill waste degradation process. Two scoring sets for landfill gas production performance are calculated with the tool including (1) methane output score which measures the deviation of the actual methane output rate at each site which the prediction generated by the first order decay model LandGEM; and (2) landfill gas indicators’ score which measures the deviation of the landfill gas indicators from their individual ideal ranges for optimal methane generation conditions. Landfill gas indicators selected include moisture content, temperature, alkalinity, pH, BOD, COD, BOD/COD ratio, ammonia, chloride, iron and zinc. A total landfill gas indicator score is also provided using multi-criteria analysis to calculate the sum of weighted scores for each indicator. The weights for each indicator are calculated using the analytical hierarchical process. The tool is tested against five scenarios for landfill sites with a range of good, average and poor landfill methane generation in one year, 2012. An interpretation of the results is given for each scenario and recommendations are highlighted for methane output rate enhancement. The scenarios used clearly illustrated how the tool can be easily used by landfill operators to enhance their understanding of methane generation at a site-specific level. The tool assists the landfill operator to track landfill methane generation over time, compare and rank sites and identify problems areas within a landfill site.
Keywords: Multi-criteria analysis; landfill assessment; landfill gas indicators; methane generation; waste management